Sammlung Speck. - Ahrens, Carsten; André, Carl; Barthes, Roland; Bauer, Wolfgang; Catoir, Barbara; Cladders, Johannes; Compton, Michael; Denizot, René; Dickhoff, Wilfried W.; Fischer, Alfred M.; Fuchs, Rudi H.; Gerdes, Ludger; et al. (Köln : Oktagon Verlag, 1996)
Andre, Carl ; Asher, Dan ; Beuys, Joseph ; Biel, Michael von ; Blum, Heiner ; Broodthaers, Marcel ; Brus, Günter ; Buren, Daniel ; Byars, James Lee ; Dahn, Walter ; Riverhead (New York) ; Förg, Gunther ; Fulton, Hamish ; Gerdes, Ludger ; Gilles, Peter ; Heerich, Erwin ; Herold, Georg ; Kawara, On ; Kiecol, Hubert ; Kippenberger, Martin ; Kirkeby, Per ; Kounellis, Jannis ; de Maria, Walter ; Merz, Mario ; Nauman, Bruce ; Nitsch, Hermann ; Oehlen, Albert ; Palermo, Blinky ; Pettibon, Raymond ; Polke, Sigmar ; Prina, Stephen ; Rainer, Arnulf ; Rehberger, Tobias ; Schlick, Jörg ; Schütte, Thomas ; Strode, Thaddeus ; Tot, Endre ; Toroni, Niele ; Trockel, Rosemarie ; Turrell, James ; Tuttle, Richard ; Twombly, Cy ; Weiner, Lawrence
biografie
Sammlung Speck, Museum Ludwig, Köln, 17. September bis 17. November 1996
Duits
boek